Measuring response to neoadjuvant chemotherapy in high-grade serous tubo-ovarian carcinoma: an analysis of the correlation between CT imaging and chemotherapy response score. Issue 5 (15th May 2019) - McNulty, Meabh; Das, Adarsh; Cohen, Paul A; Dean, Andrew
Abstract : Introduction: Response to neoadjuvant chemotherapy is measured by CT and the decision to proceed with interval surgery is made on the radiological response after two or three cycles of therapy. The Chemotherapy Response Score grades histological tumor regression in omental metastases resected at interval surgery and is associated with progression-free survival and overall survival. It is uncertain whether radiological response is associated with prognosis and whether radiological response predicts Chemotherapy Response Score. To assess if radiological response is associated with progression-free survival and overall survival. Additionally, to investigate whether radiological response predicts the Chemotherapy Response Score. Methods: Retrospective cohort study of patients with high-grade serous ovarian cancer treated with neoadjuvant chemotherapy. Radiological response was assessed by comparing CT imaging at baseline and after neoadjuvant chemotherapy using RECIST (Response Evaluation Criteria In Solid Tumors) and classified as stable disease, partial response, complete response, or progressive disease. Survival analysis was performed using Cox proportional-hazard models and the log-rank test. Results: A total of 71 patients met the inclusion criteria. Of these, 51 had pre- and post-neoadjuvant chemotherapy CT scans available for analysis. Radiological response was not associated with progression-free survival or overall survival on univariate analysis (stable disease vs partial response; HR for progression-free survival 1.15; 95% CI 0.57 to 2.32; p = 0.690; HR for overall survival 1.19; 95% CI 0.57 to 2.46; p = 0.645). In a multivariate model, radiological response was not associated with either progression-free survival (stable disease vs partial response; HR=1.19; 95% CI 0.498 to 2.85; p = 0.694) or overall survival (stable disease vs partial response; HR=0.954; 95% CI 0.38 to 2.40; p = 0.920). There was a significant association between the Chemotherapy Response Score and radiological response (p = 0.005). Discussion: A partial response and stable disease on radiological assessment after neoadjuvant chemotherapy in women with advanced high-grade serous ovarian cancer were not associated with survival, despite having a correlation with the Chemotherapy Response Score.